Strategic Core: Brand Elements and Self Development - Heri Wahyu Pratama (ITB AAS INDONESIA, 2023)
Consumer behavior at this stage has transformed a new range of suitability that benefits every brand developer. Technology has been getting closer to the ideal environmental destination in society. However, the effect is not always positive. Our study has completed the integration model on brand development research. Researcher's study on next level will have a continuing influence on the self-conformance relationship. Keywords: Consumer-brand identification, Self-concept, Generation Z, Destination quality, Strategic brand management